Carboplatin dose calculation in lung cancer patients with low serum creatinine concentrations using CKD-EPI and Cockcroft-Gault with different weight descriptors - Kaag, Dieter (Lung cancer, 2013)
Study objectives: Carboplatin dosing using the Calvert and Cockcroft-Gault formulae in patients with low serum creatinine levels is discussed controversially. We conducted a retrospective analysis applying the CKD-EPI formula and the alternate size descriptors adjusted body weight and predicted normal weight in the Cockcroft-Gault equation for calculating the carboplatin dose. Methods: Data were collected retrospectively from 128 lung cancer patients with serum creatinine <0.8mg/dL (71μmol/L) who had received chemotherapy that was mostly platinum-based. Serum creatinine concentration for renal function estimation and measured creatinine clearance (24-h urine collection) were available on the same day from these patients. Actual doses were calculated based on the Cockcroft-Gault formula with total body weight. For the study purpose doses were recalculated using Cockcroft-Gault with adjusted body weight and predicted normal weight and CKD-EPI. Subgroup analyses were performed for gender and body mass index. Results: All alternate dose calculations were not inferior to the calculation based on Cockcroft-Gault using total body weight. In overweight and obese patients they were superior in reducing mean overdose from 24% to roughly 15% (predicted normal weight, CKD-EPI) and 10% (adjusted body weight) and from 25% to 9%, 8% and 4%, respectively. Best performed the combination of Cockcroft-Gault with adjusted body weight. Conclusion: The results show that application of the alternate size descriptor adjusted body weight in the Cockcroft-Gault equation can improve dosing accuracy especially in overweight and obese patients with low serum creatinine levels.